Faktor-Faktor Yang Mempengaruhi Ketidakpatuhan Masyarakat Dalam Melaporkan SPT Tahunan Wajib Pajak Orang Pribadi (Literature Riview) - Achmad Wicaksono; Diana Sharfina; Siti Nur Syarif’ah (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
The phenomenon of non-compliance in reporting annual tax notice has become a serious concern in the tax system. The study aims to identify and examine several factors that influence public non-compliance in reporting annual tax notice, compliance strategies and personal Annual reporting arrangements. Through the analysis of related literature, the study investigates the psychological, social, economic, and regulatory factors that potentially affect tax compliance. The findings of previous research, analysis of tax regulation, public perception of tax justice, income, educational level, and other factors are the main focus in exploring the aspects that affect non-compliance behaviour. The results show that public awareness in the personal Annual notice letter report remains low even though the ratio has increased. By understanding these factors, the author hopes to provide deeper knowledge to governments and relevant agencies in designing more effective strategies to improve tax compliance. Implications of this research include better policy development as well as more appropriate persuasive efforts to promote awareness and enforcement of tax systems to be efficient.